Why should we try to think like scientists? Scientific reasoning and susceptibility to epistemically suspect beliefs and cognitive biases - Čavojová, Vladimíra; Šrol, Jakub; Jurkovič, Marek (Applied cognitive psychology, 2020)
Summary This paper examines whether scientific reasoning skills predict people's susceptibility to epistemically suspect beliefs and cognitive biases. We used the recently developed Scientific Reasoning Scale (SRS) because it measures the ability to read and evaluate scientific evidence. Alongside the SRS, 317 participants aged 18–30 years completed measures of thinking dispositions and cognitive ability to ascertain whether the SRS contributes specifically to susceptibility to epistemically suspect beliefs and cognitive biases. Scientific reasoning correlated positively with dispositions towards analytic thinking and cognitive ability and negatively with dogmatism, epistemically suspect beliefs, and susceptibility to cognitive biases. Most importantly, it emerged as a significant predictor, contributing to susceptibility to both cognitive biases and epistemically suspect beliefs over and above the other cognitive predictors. These results provide the first empirical evidence that scientific reasoning ability is an important factor in protecting against epistemically suspect beliefs and in aiding better decision making among the non‐scientific population.